(NoSNOWY KLINI^ESKOJ BIOHIMII (B/s - (NmEREVINSKIJ(B, (NmIHAIL fEDOROWI^s; (N~ERKASOWA(B, (NlIDIQ sEMENOWNAs ((NmOSKWA (B:s (NmEDICINA(B,s, 1965)
(NzAKL(B.: (NS(B. 345-347s
(NlIT(B.: (NS(B. 348-354s
Keywords: (NkLINI^ESKAQ BIOHIMIQs